A robust power flow algorithm for radial distribution systems - Eminoğlu, Ulaş; Hakan Hocaoglu, M. Hakan (My University, 2005)
In this paper, a new algorithm is presented to solve the power flow problem in radial distribution systems. The proposed method takes into account the voltage dependency of static loads, and line charging capacitance. The method is based on the forward and backward voltage calculation by using polynomial voltage equation and Kirchoff's Law for each branch. Convergence speed and reliability of the method is compared with the standard Newton-Raphson, PFLOW and Ratio-Flow method which is based on classical forward-backward ladder method. The convergence ability is also tested for different loading conditions and different R/X ratios under wide range of the exponents of the loads. Results show that the proposed algorithm is reliable, simple and has fast convergence ability. Furthermore, it is observed that the method is less sensitive to the system's parameters such as R/X ratio and loading levels. ©Copyright 2005 IEEE. © 2008 Elsevier B.V., All rights reserved.
2005 IEEE Russia Power Tech, PowerTech -- St. Petersburg -- 73241
Keywords: Polynomial equation; Power flow; Radial distribution systems; Voltage dependent loads